Exploring English Teacher Strategies to Promote Motivation in Senior High School Learners - Amalia, Riska; Sunra, La; Radhiyani, Fitri (Har Press Indonesia, 2025)
This study examines the strategies used by English teachers at SMAN 1 Barru to promote students’ motivation in learning English. Using a qualitative descriptive method, data were collected through classroom observations and interviews with teachers. The findings identify two main strategies: Active Learning and Reward Strategies. Active Learning includes group discussions, gamified quizzes, and brainstorming, which encourage student engagement, collaboration, and critical thinking. Reward Strategies involve social rewards such as verbal praise and public recognition, as well as material rewards like certificates and bonus points, all aimed at reinforcing positive learning behaviors. These strategies have significantly increased student motivation, resulting in higher levels of participation, confidence, and enthusiasm in English classes. The study offers useful insights for educators and suggests further research on the long-term impact of these strategies and additional methods to sustain motivation in diverse educational settings.